Abuse of Authority: A Meaning Deconstruction - Kurnia Dewi Anggraeny (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem:Â As part of the organization of the government duties and community services, the authority to make a decision is attributed to the government officials (inherent aan het bestuur), which has led many to become a suspect and a convict. On the other hand, it is believed that the government's policies are not subject to the law.Purpose/Objective Study: This study aims to determine to analyze abuse of authority according to a meaning deconstructionDesign/Methodology/Approach: The research applied normative juridical approach as the logical consequence of sui generis of law.Findings: Each network of a structure of meaning is always presented in the form of binary opposition. One of the elements is marginalized and abandoned. Similarly, in the field of law, the term